Public Goods and Public Allocation Policy (Allokation im marktwirtschaftlichen System, 1986)
This volume brings together 8 previously unpublished papers dealing with various modes of allocating jointly consumable goods (i.e. public goods). The issues covered range from voluntary contributions and price exclusion (market allocation) to positive and normative analyses of different political allocation procedures for public goods. Given this wide spectrum of allocative schemes for public goods there does not seem to be an easy and clear-cut message from modern public-goods theory to public allocation policy.